Parameter estimation of power system wideband oscillation based on Zoom FFT and relaxation algorithm - Shuang Feng; Yue Mei; Zhirui Zhang; Jiaxing Lei; Yi Tang (International Journal of Electrical Power & Energy Systems, 2025)
The widespread use of power electronic devices has resulted in frequent wideband oscillation events, making accurate and rapid parameter estimation critical. However, existing methods face significant challenges in balancing resolution and identification speed, especially for signals with broad frequency ranges, pronounced time-varying characteristics, and noise interference. To address these issues, this paper proposes a wideband oscillation parameter estimation method based on Zoom Fast Fourier Transform (ZFFT) and relaxation algorithm. The proposed method estimates multi-mode wideband oscillation signals by minimizing a non-linear least squares (NLS) cost function. It transforms the multi-component NLS parameter estimation problem into a series of single-component NLS parameter cyclic estimation problems. This simplification improves operational efficiency and demonstrates strong convergence and noise resistance. Additionally, to address the low accuracy in estimating wideband oscillation frequencies within a short time window, which negatively impacts the estimation accuracy of other parameters and the efficiency of algorithm iterations, the paper uses ZFFT for preliminary frequency estimation. This approach significantly improves the overall speed and accuracy of the algorithm. Results from numerical signals and measured signals from oscillation events confirm that this method effectively estimates parameters of wideband oscillation signals with high resolution, even within a short time window and in the presence of noise and multiple oscillation modes.